Expression and function of receptors for the formylated peptides in granulocytes of the patients with rheumatoid arthritis - A. Mohammad; Yu. V. Filina; R. V. Larionova; M. I. Arleevskaya; A. G. Gabdulhakova (Медицинская иммунология, 2022)
Formyl peptide receptors (FPRs) are an important part of innate immunity involved in antimicrobial phagocyte functions such as chemotaxis, secretory degranulation, and respiratory burst. These phagocyte responses are observed in both acute and systemic chronic inflammation. Abundant or constant release of pro-inflammatory ligands leads to the pre-activation of phagocytes when subsequent stimulation induces more intense cellular response. Binding of the formyl peptide receptor with its agonist activates production of reactive oxygen species, due to triggering phosphorylation of the cytoplasmic subunits p47phox and p67phox followed by their translocation to the plasma membrane and assembly into the NADPH oxidase complex. Rheumatoid arthritis is characterized by an imbalance of immune processes and autoimmune responses against the own joint tissues. It is known that, granulocytes produce increased amounts of oxygen radicals in various pathologies, including rheumatoid arthritis. We suggest that such enhancement may be due to increased expression of formyl peptide receptors or components of the FPR/PKC/NOX2 signaling pathway. Our aim was to study the mRNA expression of fpr1/fpr2 genes and the FPR-dependent production of reactive oxygen species by isolated peripheral blood granulocytes from the patients with rheumatoid arthritis. Materials and methods. The objects of the study were isolated peripheral blood granulocytes. We analyzed, respectively, 166 and 85 samples from the patients with rheumatoid arthritis and healthy donors. The production of reactive oxygen species was assessed using luminol-dependent chemiluminescence. For FPR1 activation we used a distinct concentration of the formyl peptide fMLF: the response to it was completely inhibited by pretreatment of the cells with FPR1 antagonist N-t-boc-MLF. FPR2 activation was performed by synthetic peptide WKYMVM, a specific receptor agonist. In the patients with rheumatoid arthritis, we have revealed an increased level of spontaneous and phorbol ester-induced production of reactive oxygen species by isolated peripheral blood granulocytes, thus reflecting a pre-activated state of the phagocytes in rheumatoid arthritis. We have found the increased FPR1-mediated production of oxygen radicals and expression of mRNA of fpr1 gene in blood granulocytes of rheumatoid arthritis patients. Furthermore, the enhancement of oxidase function may be associated with constitutive activation of the FPR1/PKC/NOX2 pathway as shown by positive correlation between the processes. The production of reactive oxygen species induced by stimulation of the FPR2 receptor is also increased, but it cannot be directly attributed to overexpression of the receptor mRNA or PKC/NOX2 activation, and requires further study. Understanding the mechanisms of regulation of the FPR1 and FPR2 signaling cascades may reveal new targets for anti-rheumatoid therapy.